An implementation of ICME in materials information exchanging interfaces. (June 2018) - Lin, Lianshan; Ren, Weiju
Graphical abstract: Abstract: The Integrated Computational Materials Engineering (ICME) approach provides a new paradigm for improving the performance of existing materials or discovering and developing new materials. It focuses on developing effective connections between isolated engineering fields, to bring quantitative processing-structure-property relationships and abundant validated data that populate the knowledge base for accelerating the research of new materials while reducing the cost of development. The data exchanging interfaces play a key role in building such ICME connections among different materials models, simulation tools and individual organizations. With implementations of information exchanging interface between different materials database, and interface between database and applications, this article concludes that in building effective ICME applications, 1) standards-compliant interface can improve the exchange efficiency; 2) popular web service enables automated online materials data transfer; 3) customized data interoperation scripts can provide flexibility and productivity.